2015
DOI: 10.1002/pssb.201451563
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of non‐polar m‐plane () InGaN/GaN multi‐quantum wells grown on freestanding bulk GaN

Abstract: We report on the optical properties of non-polar m-plane InGaN/GaN multi-quantum wells (MQWs) grown on ammonothermal bulk GaN substrates. The low temperature continuous wave (CW) photoluminescence spectra are broad with a characteristic low energy tail. The majority of the emission bands decay with a time constant~300 ps, but detailed photoluminescence time decay and time resolved spectroscopy measurements revealed the existence of a distinct slowly decaying emission band. This slowly decaying component is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…The data reported by Marcinkevicius et al [44] at low temperature were shown to be not influenced by nonradiative recombination. Only on the low-energy side of the spectra did we find more slowly decaying emission as we have reported elsewhere [21]. The emission on the low-energy side is attributed to semipolar QWs at step bunches described above.…”
Section: B Experimental Results: Optical Characterizationsupporting
confidence: 80%
See 2 more Smart Citations
“…The data reported by Marcinkevicius et al [44] at low temperature were shown to be not influenced by nonradiative recombination. Only on the low-energy side of the spectra did we find more slowly decaying emission as we have reported elsewhere [21]. The emission on the low-energy side is attributed to semipolar QWs at step bunches described above.…”
Section: B Experimental Results: Optical Characterizationsupporting
confidence: 80%
“…Also the intrinsic field leads to a spatial separation of electron and hole wave functions, causing a reduced radiative recombination rate [4,6], an effect that can be particularly undesirable for high-efficiency optoelectronic devices. To circumvent these effects arising from the intrinsic built-in fields, which fundamentally are caused by the growth along the polar c axis, significant research has been directed towards the fabrication of semi-and nonpolar structures [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In the case of semi-and nonpolar planes the c axis is at a nonvanishing angle with respect to the growth direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the samples discussed here were grown by metalorganic chemical vapor deposition (MOCVD), the polar sample was grown on c plane sapphire using a quasi-two temperature growth methodology which we have described in detail elsewhere, 36 and the nonpolar m-plane sample was grown on freestanding bulk GaN as described in Ref. 37. Using a CW excitation power density of 6 W/cm 2 from a He/ Cd laser, the room temperature IQE was measured using the methodology 36 of comparing the ratio of the integrated photoluminescence (PL) intensity at room temperature and 10 K. The measured ratios were 10% and 20% for the c-plane and m-plane samples, respectively.…”
Section: à2mentioning
confidence: 99%
“…Comprehensive details of the quasi-two temperature 30 growth schedule and structural details of this sample can be found elsewhere. 32 The polar sample is a c-plane InGaN/GaN single QW structure grown on a (0001) sapphire substrate with an In fraction of 0.15 and a thickness of 2.9 nm at a temperature of 750 C using a single temperature growth methodology. 33 The structural properties of the c-plane sample are further described in Ref.…”
Section: à2mentioning
confidence: 99%